2006
DOI: 10.1111/j.1365-246x.2006.03050.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal velocity structure of the British Isles; a comparison of receiver functions and wide-angle seismic data

Abstract: SUMMARY Magmatic underplating at the base of the continental crust is thought to be an important consequence of mantle plume activity. Geochemical evidence supports the hypothesis of underplating beneath the British Tertiary Igneous Province during Palaeocene times, a process that has been invoked to explain at least part of the observed pattern of Cenozoic denudation and consequent offshore deposition. This study uses receiver functions to independently test the results of modelling of four wide‐angle seismic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The crustal model for the Irish crust, presented in this study, shows a subdivision of the lower crust into two distinct layers with an aggregate thickness of about 10 km and with a uniform Poisson's ratio (σ= 0.257–0.265) diagnostic of an unusual felsic composition (Figs 9, 10 and 12). There is no unambiguous seismological evidence for a significant mafic (underplated) component within the lower crust or near its base, as has been inferred on the basis of receiver function studies, which are partially constrained by wide‐angle seismic data beneath Ireland (Shaw Champion et al 2006). The rare enigmatic mafic granulite xenoliths, which the thermobarometric studies indicate are sourced from close to or below the present‐day seismic refraction Moho (Van den Berg et al 2005), have uncertain geochemical affinities.…”
Section: Discussionmentioning
confidence: 99%
“…The crustal model for the Irish crust, presented in this study, shows a subdivision of the lower crust into two distinct layers with an aggregate thickness of about 10 km and with a uniform Poisson's ratio (σ= 0.257–0.265) diagnostic of an unusual felsic composition (Figs 9, 10 and 12). There is no unambiguous seismological evidence for a significant mafic (underplated) component within the lower crust or near its base, as has been inferred on the basis of receiver function studies, which are partially constrained by wide‐angle seismic data beneath Ireland (Shaw Champion et al 2006). The rare enigmatic mafic granulite xenoliths, which the thermobarometric studies indicate are sourced from close to or below the present‐day seismic refraction Moho (Van den Berg et al 2005), have uncertain geochemical affinities.…”
Section: Discussionmentioning
confidence: 99%
“…The ZK technique has been applied worldwide in multiple studies (e.g., FRANÇA and ASSUMPÇ AO 2004;GEISSLER et al 2008;PIANA AGOSTINETTI and AMATO 2009;LLOYD et al 2010;GALLACHER and BASTOW 2012) and is a well-established method to estimate depths and V p /V s ratios for simple crustal structures. Complex tectonic environments prove to be a challenge for ZK technique, since the RF time series are composed of a multitude of converted phases due to the occurrence of several seismic discontinuities in the crust (e.g., CHAMPION et al 2006). Due to the intricate structure of the Eastern Alps, we chose to constrain the results by keeping the V p /V s ratio constant and invert for Moho depths only.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic anisotropy in the continental crust has been observed in numerous seismological studies, and many workers seek to relate the observed seismic anisotropy to crustal deformation and metamorphism (e.g. Okaya et al 1995; Weiss et al 1999; Godfrey et al 2000; Okaya & Christensen 2002; Okaya & McEvilly 2003; Vergne et al 2003; Ozacar & Zandt 2004; Shapiro et al 2004; Sherrington et al 2004; Lloyd & Kendall 2005; Champion et al 2006; Mahan 2006; Mainprice 2007; Xu et al 2007; Lloyd et al 2009; Readman et al 2009).…”
Section: Introductionmentioning
confidence: 99%